(untitled) (Revista de História Regional, 2020)
This article analyzes the changes in social relations between residents of two riverside cities, Aragarças (GO) and Barra do Garças (MT). Different the early days when the relationship between the urban centers of Barra Goiana and Barra Cuiabana - names of origin of both cities - was friendly and there was a common past shared, it was transformed into a stage of symbolic and identity disputes from the 1960s. The search for social, economic and political prestige led to the construction of a new representative and identity order. The progressive discourse based on the government’s developmental programs in the region brought about a change that altered the way of seeing and representing the other, changing in distinction the similarity that existed between the two urban centers.